Four new species of Parajapyx (Diplura: Parajapygidae) from Mexico with redescription of Parajapyx isabellae aztecus Silvestri - Montejo-Cruz, Maira; García-Gómez, Arturo; Palacios-Vargas, José G. (Zootaxa, 2021)
Four new Mexican Parajapyx species are described: P. silvestrii sp. nov. differs from P. adisi Pagés by the presence of one ma macroseta on mesoscutum, metascutum and abdominal scutum I; P. pagesi sp. nov. differs from P. grassianus Silvestri in the arrangement and number of macrosetae on all abdominal scuta; P. brunocondei sp. nov. is characterized by the unique feature of 50 glandular setae on the subcoxal organs and femur with one macroseta; P. yunyanorum sp. nov. differs from P. reymi Pagés by having some reduced macrosetae on the mesoscutum and metascutum and one lp macroseta lacking on abdominal II to VII scuta. A redescription of P. isabellae aztecus Silvestri, 1948 is presented including additional characters not previously reported, such as complete body chaetotaxy and descriptions of leg III, antennae and cercus. An identification key is presented for Mexican species of Parajapyx.